2020
DOI: 10.1111/pin.12975
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of microRNA expression during the progression of colorectal tumors

Abstract: MicroRNAs (miRNAs) are potential biomarkers of neoplastic lesions, but additional information on dysregulated miRNA expression during progression of the adenoma–adenocarcinoma sequence may be helpful to identify the role of miRNAs in this sequence. We examined the expression levels of 13 miRNAs (hsa‐miRNA‐19a‐3p, hsa‐miRNA‐21‐5p, hsa‐miRNA‐27a‐3p, hsa‐miRNA‐27b‐3p, hsa‐miRNA‐31‐5p, hsa‐miRNA‐34b‐3p, hsa‐miRNA‐125b‐5p, hsa‐miRNA‐143‐3p, miRNA‐191‐5p, hsa‐miRNA‐193b‐3p, hsa‐miRNA‐195‐5p, hsa‐miRNA‐206 and hsa‐le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Classical adenomas are precursor lesions characterized by hyperplastic and dysplastic epithelial cells with increased malignant transformation potential [ 7 ]. Colorectal tumorigenesis is considered a multistep process in which genetic changes continue to accumulate, eventually resulting in an aggressive phenotype (adenoma–carcinoma sequence) [ 8 ]. Statistical analysis showed that the 5-year survival rate of patients with stage I CRC was over 90% and that of patients with stage IV CRC was only 10% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Classical adenomas are precursor lesions characterized by hyperplastic and dysplastic epithelial cells with increased malignant transformation potential [ 7 ]. Colorectal tumorigenesis is considered a multistep process in which genetic changes continue to accumulate, eventually resulting in an aggressive phenotype (adenoma–carcinoma sequence) [ 8 ]. Statistical analysis showed that the 5-year survival rate of patients with stage I CRC was over 90% and that of patients with stage IV CRC was only 10% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though without the ability to transcribe into proteins, miRNAs regulate gene expression at both the transcriptional and post-transcriptional levels [ 13 ]. Alternations in miRNA levels and activities have been observed in many cancer cells [ 14 ]. Benefited from the small size and hairpin-loop structure, microRNAs are protected from degradation and their levels might be used as diagnostic and prognostic markers of cancer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%